An Analysis of School Principals’ managerial Functions in Implementing the Merdeka Curriculum at SD Islam Al Furqon Rembang - Ali Wahyudi; Ali Shodiqin Ali Shodiqin; Soedjono Soedjono (FKIP - Universitas Riau, 2026)
The implementation of the Merdeka Curriculum requires effective school leadership to support educational transformation and improve learning quality. The principal’s managerial functions play a crucial role in ensuring that curriculum implementation is carried out systematically and sustainably. This study aims to analyze the managerial functions of the principal in implementing the Merdeka Curriculum at SD Islam Al Furqon Rembang. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and document analysis and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the principal effectively performs four managerial functions. In planning, the principal conducts school self-evaluations, formulates goals, and aligns school programs with the Merdeka Curriculum. In organizing, tasks are delegated according to teachers’ competencies to promote collaboration and efficiency. Through actuating, the principal motivates and guides teachers in implementing innovative learning practices. In controlling, the principal monitors and evaluates instructional activities and uses evaluation results to support continuous improvement. The study concludes that the successful implementation of the Merdeka Curriculum is strongly influenced by the principal’s ability to integrate managerial functions systematically, contributing to improved teaching and learning quality.